Relevansi Instrumen Hak Asasi Manusia Internasional Terhadap Pelindungan Hukum Pekerja Migran Perempuan Indonesia Di Negara Tujuan - Muhammad Abas; Wike Nopianti (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
BNP2TKI data shows that since the 1990s, Indonesian migrant workers have been predominantly women, comprising 69–75% annually. This study applies a normative juridical method with a gender-sensitive legal analysis approach to examine international legal norms and their responses to the vulnerabilities of women migrant workers. The findings reveal that states’ positive obligations have instead created loopholes to evade responsibility through legal techniques and jurisdictional complexities. Diplomatic protection, which should safeguard citizens abroad, has shifted into a bargaining tool in bilateral relations that prioritize economic-political interests over human rights. ASEAN cooperation likewise emphasizes economic integration rather than human rights protection, as reflected in the ASEAN Consensus, which is declarative rather than binding. Both national and regional implementation demonstrate a significant gap between normative commitments and practical realities, driven by states’ structural resistance, economic-political conflicts of interest, and paternalistic-formalistic approaches that fail to address systemic vulnerabilities rooted in gender and migrant status. This crisis of legitimacy within international human rights instruments reflects a structural failure of protection systems that rely too heavily on the state as the primary actor, even though states are often perpetrators or enablers of exploitation.